2017
DOI: 10.1007/s00442-017-3831-6
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that higher [CO2] increases tree growth sensitivity to temperature: a comparison of modern and paleo oaks

Abstract: To test tree growth sensitivity to temperature under different ambient CO concentrations, we determined stem radial growth rates as they relate to variation in temperature during the last deglacial period, and compare these to modern tree growth rates as they relate to spatial variation in temperature across the modern species distributional range. Paleo oaks were sampled from Northern Missouri, USA and compared to a pollen-based, high-resolution paleo temperature reconstruction from Northern Illinois, USA. Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 104 publications
0
12
0
Order By: Relevance
“…The apparent absence of an eCO 2 effect on tree allometry is surprising because tree geometry, and in particular the relationship between diameter and height, has been shown to be affected by other environmental factors (Chave et al, ; Duncanson, Dubayah, & Enquist, ; Hulshof, Swenson, & Weiser, ; Ibáñez, Zak, Burton, & Pregirzer, ; Lines, Zavala, Purves, & Coomes, ; Samuelson et al, ; Voelker et al, ; Way & Oren, ). For example, the DBH– H relationship may be modulated by plant–water relations.…”
Section: Introductionmentioning
confidence: 99%
“…The apparent absence of an eCO 2 effect on tree allometry is surprising because tree geometry, and in particular the relationship between diameter and height, has been shown to be affected by other environmental factors (Chave et al, ; Duncanson, Dubayah, & Enquist, ; Hulshof, Swenson, & Weiser, ; Ibáñez, Zak, Burton, & Pregirzer, ; Lines, Zavala, Purves, & Coomes, ; Samuelson et al, ; Voelker et al, ; Way & Oren, ). For example, the DBH– H relationship may be modulated by plant–water relations.…”
Section: Introductionmentioning
confidence: 99%
“…In view of this increase in performance and productivity promoted by high [CO 2 ], even in the presence of abiotic stresses, should we really be concerned about the dynamics of the distribution and survival of forest species under a climate change scenario? The answer to this question is extremely complex because the beneficial effects of high [CO 2 ] found in some studies (Drake et al, 2011;Idso & Kimbal, 1997;Oliveira et al, 2016;Pérez-Jiménez, Hernández-Munuera, Piñero, López-Ortega, & del Amor, 2018;Radoglou & Jarvis, 1990;Rodrigues et al, 2016;Roy et al, 2016;Swann et al, 2016;Yu et al, 2014) are in direct contrast to the results of several other reports (Calvo et al, 2017;Clark, Clark, & Oberbauer, 2010;Faralli et al, 2017;Feeley, Joseph Wright, Nur Supardi, Kassim, & Davies, 2007;Voelker et al, 2017).…”
Section: The Controver S Ial Role Of C Arbon D I Oxide: a P Otentiamentioning
confidence: 99%
“…The same scenario of uncertainties about the mitigating effect of high [CO 2 ] is also observed for plants exposed to high temperatures, particularly when this stress is associated with drought (Becklin et al, ; Duan et al, ). Under these conditions, increased leaf area and reductions in transpiration rates can significantly reduce latent heat loss, which may increase leaf temperature and subsequently generate a series of disturbances that may enhance vulnerability to heat stress (e.g., increase in R and P R rates; Voelker et al, ) (Figure ).…”
Section: The Controversial Role Of Carbon Dioxide: a Potential Friendmentioning
confidence: 99%
“…and surface resistance of 70 s/m [48]. Noteworthily, increasing evidences from observations and modellings have confirmed that several indicators (e.g., stomatal resistance and LAI) of plant structure and physiology have varied with changing climate and increasing CO 2 level, in spite of some uncertainties and differences (e.g., magnitude of stomatal resistance and LAI variations) among various plants [73][74][75][76][77]. en, incomplete considerations of plant responses would like to impact our results and the dryness/wetness-related researches [78].…”
Section: Uncertaintiesmentioning
confidence: 99%